Extralegal Punishment Factors: A Study of Forgiveness, Hardship, Good-Deeds, Apology, Remorse, and Other Such Discretionary Factors in Assessing Criminal Punishment - Bartels, Daniel M. (2012)
The criminal law's formal criteria for assessing punishment are typically contained in criminal codes, the rules of which fix an offender's liability and the grade of the offense. A look at how the punishment decision-making process actually works, however, suggests that courts and other decisionmakers frequently go beyond the formal legal factors and take account of what might be called extralegal punishment factors (XPFs). XPFs, the subject of this Article, include matters as diverse as an offender's apology, remorse, history of good or bad deeds, public acknowledgment of guilt, special talents, old age, extralegal suffering from the offense, as well as forgiveness or outrage by the victim, and special hardship of the punishment for the offender or his family. Such XPFs can make a difference at any point in the criminal justice process at which decisionmakers exercise discretion, such as when prosecutors decide what charge to press, when judges decide which sentence to impose, when parole boards decide when to release a prisoner, and when executive officials decide whether to grant clemency, as well as in less-visible exercises of discretion, such as in decisions by police officers and trial jurors. After a review of the current use and rationales behind eighteen common XPFs, in Part I, the Article reports in Part II the results of an empirical study of lay intuitions regarding the propriety of taking such factors into account in adjusting the punishment that otherwise would be imposed, the extent of any adjustment to be made, as well as an assessment of how the views might change with different kinds of offenses and how they might vary with demographic factors. Part III examines the implications of the study findings for current law and practice, with special attention to the problem of disparity in application that is invited by the high levels of disagreement on the proper role of some XPFs and the problem of conflicts between lay intuitions and current law and practice. It is not uncommon that there is strong support for reliance upon XPFs that current practice ignores and little support for reliance upon XPFs the current practice commonly relied upon